Endometriosis and irritable bowel syndrome: similarities and differences in the spectrum of comorbidities. Issue 9 (17th June 2022) - Peters, M; Mikeltadze, I; Karro, H; Saare, M; ,; Salumets, A; Mägi, R; Laisk, T
Abstract: STUDY QUESTION: Do the spectrum and prevalence of comorbidities of endometriosis and irritable bowel syndrome (IBS) overlap? SUMMARY ANSWER: Despite several overlapping symptoms, the most significantly associated comorbidities of endometriosis and IBS are different and are rather related to the organ systems primarily involved in the index diagnosis. WHAT IS KNOWN ALREADY: Endometriosis and IBS both have several similar unspecific symptoms, such as recurrent abdominal pain, cramping and anxiety, and both diseases affect young women and are associated with a number of comorbidities causing a poor quality of life. However, a detailed study, revealing the full spectrum of endometriosis and IBS comorbidities in the same study population, is lacking. STUDY DESIGN, SIZE, DURATION: This article presents a retrospective in silico analysis of the data from a large nationwide biobank-based cohort consisting of 121 773 women. After excluding all first- and second-degree relatives, the data of up to 65 421 women were analyzed. PARTICIPANTS/MATERIALS, SETTING, METHODS: International Classification of Disease-10 diagnosis main codes associated with endometriosis (N80) and IBS (K58) diagnoses were identified from the Estonian Biobank dataset by linking with the Estonian Health Insurance Fund and other relevant registries. The associations between N80 and K58 and other diagnosis codes were tested using logistic regression, adjusting for age at recruitment and 10 genetic principal components to account for potential population stratification. Bonferroni correction was applied to account for multiple testing. MAIN RESULTS AND THE ROLE OF CHANCE: Both women with endometriosis and IBS suffered from more conditions compared to the control group, with 226 and 428 diagnosis codes statistically significantly more frequent in women with respective diagnosis compared to controls. Women suffering from both conditions had 275 significantly associated comorbidities. A remarkable proportion of women with IBS or endometriosis suffered also from endometriosis (9.0%) or IBS (13.6%), respectively. In endometriosis, the most prevalent diagnoses were related to diseases of the genitourinary system (33 N-category codes) and in women with IBS, the most associated diagnoses were related to digestive disorders and gastrointestinal tract (52 codes from K-category). Among the most significant diagnoses in endometriosis were uterine leiomyomas (D25), menstrual disorders (N92) and infertility (N97) ( P  < 1 × 10 −315 for all), and in IBS, lactose intolerance (E73), gastritis and duodenitis (K29) and functional dyspepsia (K30) were in the top list of most significant comorbidities ( P  < 1 × 10 −315 for all). LIMITATIONS, REASONS FOR CAUTION: The information about the severity stages of endometriosis and subtypes of IBS was not available for analysis. The findings may not be fully extrapolated to all female populations, because all participants were from one geographic area and had good access to health services. WIDER IMPLICATIONS OF THE FINDINGS: These findings support previous studies that have found a high prevalence of pre-selected comorbidities in women with endometriosis and IBS. However, taking into account the differences in the full spectrum of comorbidities of endometriosis and IBS may aid in diagnosing these disorders. Women and healthcare providers need to be aware that women with endometriosis are at high risks of complications during pregnancy and should be carefully monitored. STUDY FUNDING/COMPETING INTEREST(S): This research was funded by the Estonian Research Council (grant PRG1076), Horizon 2020 innovation grant (ERIN, grant no. EU952516), Enterprise Estonia (grant no. EU48695), MSCA-RISE-2020 project TRENDO (grant no. 101008193) and by the European Union through the European Regional Development Fund (Projects no. 2014-2020.4.01.15-0012 and no. 2014-2020.4.01.16-0125). The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.